Design of Aqidah Learning System Collaborative Learning Based Morals to Improve Students' Social Skills - Najamudin Najamudin; Surahman Hidayat; Mufidatul Azizah (International Journal of Islamic Educational Research, 2024)
collaborative learning -based aqidah akhlak learning system in improving students' social skills. In the era of globalization, social skills are one of the important aspects in the formation of students. Collaborative learning not only focuses on academic achievement but also on the development of communication skills, cooperation, and empathy. The method used in this study is library research from various sources related to the research topic. Data collection is carried out through studies, research, analysis of scientific articles, books, journals or magazines and electronic sources related to collaborative learning-based aqidah akhlak learning . The data is then analyzed descriptively. Results from review library research shows that collaborative learning is an approach that emphasizes cooperation between students in groups to achieve common learning goals. Collaborative learning strategies in Islamic religious education are approaches that prioritize interaction and cooperation between students to achieve a deeper and more holistic understanding of the teaching material. Well-designed learning will make it easy to overcome behavior in students. The application of collaborative learning not only improves students' understanding of the concept of aqidah and akhlak, but also strengthens their social skills. The importance of social interaction, student involvement actively in the learning process, discussing, and working together in solving case studies of the concept of aqidah and akhlak. By implementing the method, it can be an effective strategy in improving student cooperation and students are better able to understand the material of aqidah and akhlak in depth and apply Islamic values in everyday life and can be applied more widely in Educational context religion Islam.